2018
DOI: 10.1159/000485180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gene Variants Controlling Vitamin D Metabolism and Serum Levels on Hepatic Steatosis

Abstract: Background/Aims: Common genetic variations in vitamin D metabolism are associated with liver stiffness. Whether these genes are implicated in hepatic steatosis remains unclear. Here we aimed to analyse the association of common vitamin D pathway gene variants with liver steatosis. Methods: Liver steatosis was assessed non-invasively in 241 patients with chronic liver conditions by controlled attenuation parameter (CAP). The following polymorphisms were genotyped using TaqMan assays: group-specific component (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Interestingly, variations of genes involved in vitamin D metabolism pathway described above have been shown to be associated with many conditions, such as coronary artery disease, osteoporosis, diabetes and autoimmune diseases, indicating the interaction between this pathway and health outcomes [16][17][18][19]. Additionally, a number of studies have reported the association between vitamin D-related genetic variations and NAFLD [20][21][22][23][24][25][26][27][28][29][30][31]. The objective of this systematic review was therefore to identify and summarize the results of all available studies that explored the association of vitamin D-related genetic polymorphisms with presence, severity and response to treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, there were only nine cases with chronic C hepatitis, including six cases associated with hepatocellular carcinoma. For patients with vitamin D deficiency, recent studies have suggested that a genetic relationship between patients with VDR and CYP2R1 gene variants may be linked to the deficiency [ 11 , 12 ]. Our recent study showed that VDR rs2228530 genetic alleles with AA and AG may be associated with the development of non-alcoholic fatty liver disease after LDLT [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Levels of ALT is usually a marker of hepatocellular injury [ 43 ]. However, levels of blood biochemical indexes, like ALT, AST, ALP, GGT, and TBIL, are not able to predict NC-induced liver injury in our study.…”
Section: Discussionmentioning
confidence: 99%